Identification of C5+ extraband of butyrylcholinesterase and two protein bands cathodic to it (Faculty of Medicine Universitas Indonesia, 2001)
Electrophoresis of human plasma yields 4 butyrylcholinesterase (BChE) protein bands, i.e. C1, C2, C3, C4 and in some individuals also an extraband C5+. In addition to that other protein bands called